2017
DOI: 10.1039/c6ra27987b
|View full text |Cite
|
Sign up to set email alerts
|

Biocomposite consisting of miscanthus fiber and biodegradable binary blend matrix: compatibilization and performance evaluation

Abstract: Biocomposites were fabricated from miscanthus fibers and a blend composed of poly(butylene succinate) (PBS)/poly(butylene adipate-co-terephthalate) (PBAT) matrix by extrusion and injection molding. Due to the reinforcing effect of miscanthus fibers, the tensile, flexural, and storage modulus of the composites were increased with increasing fiber content from 30 to 50 wt%. Young's modulus of the composite was evaluated by parallel, series, Hirsch and Halpin-Tsai models. It was found that the Hirsch model has go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 48 publications
10
44
0
Order By: Relevance
“…The MAH‐ g ‐PBAT and PBAT/miscanthus composites did not show significant difference in the melting and glass transition temperature. In our previous study, we have found similar observation in the PBS/miscanthus composites . The crystallization temperature of the PBAT is around 80 °C [Figure (B)].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The MAH‐ g ‐PBAT and PBAT/miscanthus composites did not show significant difference in the melting and glass transition temperature. In our previous study, we have found similar observation in the PBS/miscanthus composites . The crystallization temperature of the PBAT is around 80 °C [Figure (B)].…”
Section: Resultssupporting
confidence: 78%
“…The storage modulus of the PBAT is 2 GPa at −45 °C whereas the PBAT/miscanthus fiber composites have storage modulus of 2.75 GPa at −45 °C (Figure ). There was a sharp reduction is storage modulus of the PBAT and its composites at −20 °C because of the molecular chain mobility increased at glass transition temperature . The PBAT/miscanthus composites showed significantly higher storage modulus than neat PBAT up to 100 °C.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…PBAT is synthesized from 1,4‐butanediol, terephthalic acid, and adipic acid monomers by polycondensation reactions . PBAT demonstrates good flexibility with a melting and glass transition temperature of 120 and −17 °C, respectively .…”
Section: Biodegradable Polymersmentioning
confidence: 99%
“…The elongation at the break of PPC was drastically reduced with 10 wt% HPF and plateaued with a further increase in HPF content up to 40 wt%. This phenomenon is a typical characteristic of short fiber reinforced composites . In another study, biocomposites were prepared from PPC polymer with Caulis Spatholobi residue fiber (CSRF).…”
Section: Ppc Compositesmentioning
confidence: 99%